ChemInform Abstract: Five‐Fold Symmetric Penta‐Substituted Corannulene with Gelation Properties and a Liquid‐Crystalline Phase. Issue 50 (10th December 2013) - Mattarella, Martin; Haberl, Johannes M.; Ruokolainen, Janne; Landau, Ehud M.; Mezzenga, Raffaele; Siegel, Jay S.
Abstract Compounds Ia‐c are prepared in a three step sequence.